1988
DOI: 10.1080/00359198809520133
|View full text |Cite
|
Sign up to set email alerts
|

Use of Protein Electrophoresis in Evolutionary Systematics

Abstract: This paper explores the use of genotypic data derived by protein electrophoresis in taxonomic and phylogenetic research. Variation in the electrophoretic mobilities of proteins can be used as a measure of nucleotide sequence variation in nuclear DNA. The resulting Mendelian data are useful for identifying morphologically cryptic species and for inferring phylogenetic relationships among congeneric species or closely related genera. Two methods, phenetics and cladistics, can be used to make phylogenetic inferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The result of the electrophoretic binding pattern of the studied accession of Bambara groundnut revealed some diagnostic characteristics that could be used for taxonomic decision. Similarities and differences observed in this work agreed with the studies of Grant et al, 1988 who adopted protein electrophoresis in evolutionary systematics; Massawe et al 2002;Modini et al 2006and Agbolade et al 2013and 2017, who at both studies employed comparative electrophoretic protein banding pattern of different species and accessions in establishing relation among various taxa.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The result of the electrophoretic binding pattern of the studied accession of Bambara groundnut revealed some diagnostic characteristics that could be used for taxonomic decision. Similarities and differences observed in this work agreed with the studies of Grant et al, 1988 who adopted protein electrophoresis in evolutionary systematics; Massawe et al 2002;Modini et al 2006and Agbolade et al 2013and 2017, who at both studies employed comparative electrophoretic protein banding pattern of different species and accessions in establishing relation among various taxa.…”
Section: Resultssupporting
confidence: 90%
“…It's worthwhile to emphasize that ultimately and logically differences in electrophoresis mobility of protein fractions from two sources are of greater importance for taxonomic purposes than the similarities of mobility. The possibility of two dissimilar proteins having identical electrophoretic mobility is known (Grant et al, 1988;Agbolade et al, 2013), yet the assumption is made that bands derived from two accession that migrate the same distance in Bambara groundnut are considered to be produced by gene(s) common to both accessions. The student T-test revealed that accessions B, C, E, F, H and I have molecular weights not significantly different from one another (p<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The widespread use of allozymes has contributed signi®cantly towards our understanding of genetic variation in natural populations and has been used to conclude systematic debates (Grant, Dempster & Da Silva, 1988). The widespread use of multivariate morphometrics in systematics has revitalized this ®eld in recent years (Rohlf & Marcus, 1993 different dentition patterns in freshwater crabs and the measurements used in the present study.…”
Section: Introductionmentioning
confidence: 98%
“…Among the methods that are commonly used in invertebrate systematics is allozyme electrophoresis (Thorpe & Sole Cava, 1994). The widespread use of allozymes has contributed signi®cantly towards our understanding of genetic variation in natural populations and has been used to conclude systematic debates (Grant, Dempster & Da Silva, 1988). The widespread use of multivariate morphometrics in systematics has revitalized this ®eld in recent years (Rohlf & Marcus, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The average genetic distance of the 15 species in the genus Vigna is 0.52. This value is slightly more than the average genetic distance expected (0.40) for species within the same genus (Grant et al, 1988). One important aspect of this study is that the seven (7) landraces of Bambara groundnut were placed in two separate clusters (Figures 6 and 7) implying that there is variation of rDNA gene units between the landraces.…”
Section: Phylogenetic Analysismentioning
confidence: 52%